2015
DOI: 10.1007/s12257-013-0845-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of nutrients and LED light intensities on biomass production of microalgae Chlorella vulgaris

Abstract: Microalgae are viable sources of biological compounds for biodiesel production. In this study, effects of various types of nitrogen sources and nutrients concentrations in the growth medium and different LED light wavelengths and intensities on biomass production of green algae Chlorella vulgaris were investigated. Warm white light with 80 µmol/m 2 /sec light intensity was determined as the optimal light for biomass production. The results indicated that microalgae growth with urea as nitrogen source was highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 37 publications
4
32
0
1
Order By: Relevance
“…Macroalgae demonstrate multiple groups of eukaryotic, photosynthetic, and aquatic organisms. The macroalgae species are multicellular with plant‐like specifications and are known as seaweeds . The common appearance of macroalgae structures is extremely diverse.…”
Section: Algaementioning
confidence: 99%
See 1 more Smart Citation
“…Macroalgae demonstrate multiple groups of eukaryotic, photosynthetic, and aquatic organisms. The macroalgae species are multicellular with plant‐like specifications and are known as seaweeds . The common appearance of macroalgae structures is extremely diverse.…”
Section: Algaementioning
confidence: 99%
“…Since microalgae are photosynthetic organisms, they need a light source for their growth . They can easily capture CO 2 gas and convert it to high value by‐products like carbohydrates, lipids, and vitamins , .…”
Section: Algaementioning
confidence: 99%
“…BTA 9031 was able to grow in media containing 0.75 gL 21 sodium nitrate which ultimately reduces the cultivation cost to certain extent. Khalili et al (2015) reported the use of ammonium chloride and ammonium carbonate as a source of nitrogen for cultivation of C. vulgaris. Results revealed that 0.236 gL 21 of ammonium chloride and 0.212 gL 21 of ammonium carbonate produced a biomass of 0.50 and 0.40 gL 21 , respectively.…”
Section: Effect Of Different Nitrogen and Phosphatementioning
confidence: 99%
“…Results revealed that 0.236 gL 21 of ammonium chloride and 0.212 gL 21 of ammonium carbonate produced a biomass of 0.50 and 0.40 gL 21 , respectively. When compared to ammonium chloride and ammonium carbonate, sodium nitrate proved to a better nitrogen source because it helped produce a much higher biomass of 0.789 gL 21 at the end of cultivation [26].…”
Section: Effect Of Different Nitrogen and Phosphatementioning
confidence: 99%
“…[20] Its main commercial application is lipid production [21] for biofuel. [22] The storage location [23] and pathways for lipid [24] and carotenoid [25] synthesis differ, therefore, it is unlikely that lipid production will influence carotenoid measurements. Additionally, lipid Raman spectra [26] differ from carotenoid Raman spectra and can be easily spotted, if present.…”
Section: Introductionmentioning
confidence: 99%